Sintesis dan Karakterisasi Karbon Aktif dari Ampas Tebu Diaktivasi menggunakan Gelombang Mikro - Hendra Zalmi; Miftahul Khair (Jurnal Periodic Jurusan Kimia UNP, 2021)
Synthesis of activated carbon and physical activation using microwaves. Sugarcane bagasse is carbonized at a temperature of 250 oC for ninety minutes and is activated using microwaves which refer to the principles of green chemistry. Microwave one of the electromagnetic waves that can be at a frequency of 2450 khz. Microwaves are able to work as activator of 450 watts of activated carbon for two minutes and the iodine number is from 203.0560 mg / g to 836.9365 mg / g which meets the indonesian national standard no 06-3730-1995 which is 750 mg / g. Activated carbon was characterized optimally using a FTIR spectrophotometer. The spectra results show the presence of a functional group -OH at wave number 3350-3252 cm-1, C=C at wave number 1570-1320 cm-1, C-O at wave number 1300-900 cm-1, and ch at wave number 995-670 cm-1. Adsorption of activated carbon against rhodamine dye obtained optimal conditions with a concentration of 350 mg / L, time of 120 minutes which has an adsorption capacity of 7.251724 mg / g.